A case of anaphylaxis induced by intravenous hydrocortisone - Lopes,Ana G. (2024)
Abstract Our case focuses on a 34-year-old woman, pregnant, with a history of allergic rhinitis treated with antihistamines as needed. She had no documented history of medication allergies. At 38 weeks she went into labor. Three days after delivery, she received intravenous hydrocortisone for postpartum pain management. During administration, the patient developed generalized urticaria, dysphonia, and dyspnea. She was brought to the emergency room and received intramuscular adrenaline and antihistamines with clinical improvement. Prick tests for methylprednisolone succinate 10 mg/ml and hydrocortisone succinate 10 mg/mL and 100 mg/ml were positive. In challenge testing, the patient tolerated dexamethasone and budesonide. A diagnosis of anaphylactic reaction to group A corticosteroids was made. The patient was instructed to avoid hydrocortisone, methylprednisolone, and prednisolone. Although rare, corticosteroid allergy has very important therapeutic consequences; therefore it is necessary to be alert and to offer a safe alternative to these patients demonstrating tolerance to other corticosteroids.